A focusing MUSIC algorithm for baseline-free Lamb wave damage localization. (1st February 2022) - Xu, Caibin; Wang, Jishuo; Yin, Shenxin; Deng, Mingxi
Abstract: The dispersion effect of Lamb waves can cause different degree of phase distortion of array signals, which will make the classical multiple signal classification (MUSIC) algorithm no longer valid in Lamb wave based damage localization. At the same time, baseline subtraction and estimation of the number of scattering sources are required in the classical MUSIC algorithm, which limits its application. A focusing MUSIC algorithm is proposed for baseline-free Lamb wave damage localization on isotropic materials. Based on the virtual time reversal technique, the dispersive wave packets adaptively back propagate according to their respective propagation distances so that the dispersion can be completely compensated and focusing signals are obtained. Wave packet truncation is implemented on the focusing signals and then let the truncated signals forward propagate with the group velocity at center frequency. The two operations, back propagation and forward propagation, can compensate the dispersion effect and avoid estimating of the number of scattering sources as well as baseline subtraction. Experiments are conducted on an aluminum plate to investigate the performance of the proposed algorithm. A uniform linear PZT array is glued on the aluminum plate to transmit and receive Lamb waves. Experimental results of the proposed algorithm as well as the classical MUSIC algorithm are given and compared. The comparison verifies the effectiveness of the proposed focusing MUSIC algorithm. Highlights: A focusing MUSIC algorithm for Lamb wave damage localization is proposed. The proposed algorithm is baseline-free. The number of scattering sources is not required to estimate.